Carbon–TiO₂ Hybrid Photocatalysts: Roles of Carbon Types in Enhancing Photocatalytic Performance - Devi Lestari; Imas Masriah; Juli Novita Sari; Amru Daulay (Politeknik Negeri Medan, 2026)
Titanium dioxide (TiO₂) is one of the most extensively studied semiconductor photocatalysts due to its chemical stability, non-toxicity, and strong oxidizing ability. However, its practical application is hindered by a wide band gap ( 3.2 eV for anatase), rapid charge carrier recombination, and limited visible-light response. The integration of various carbon-based materials with TiO₂ has emerged as a highly effective strategy for overcoming these limitations. This review systematically examines the distinct roles played by different carbon allotropes and carbon-based materials including graphene, reduced graphene oxide (rGO), carbon nanotubes (CNTs), carbon quantum dots (CQDs), graphitic carbon nitride (g-C₃N₄), activated carbon (AC), and biochar when hybridized with TiO₂. The mechanisms by which each carbon type enhances photocatalytic performance are critically analyzed, encompassing improved charge carrier separation, extension of light absorption to the visible region, elevated pollutant adsorption through synergistic effects, and the formation of unique heterojunction architectures. Furthermore, recent advances in synthesis methodologies, key photocatalytic applications in environmental remediation and energy conversion, and structure–activity relationships are comprehensively reviewed. Challenges pertaining to scalability, stability, and carbon loading optimization are identified, and future research directions are proposed. This review provides a unified framework for understanding how the structural and electronic properties of carbon materials govern the photocatalytic behavior of Carbon–TiO₂ hybrids, guiding the rational design of next generation photocatalysts.